Degradation of Polyethylene terephthalate by Ethanol - Krangekrikissada, Wanlop; W.Lothongkum, Anchaleeporn (Engineering and Applied Science Research, 2013)
This work studied the degradation of polyethylene terephthalate by ethanol with and without catalysts. The degradation without catalyst, PET was introduced into an autoclave with ethanol and heated at the temperature of 220º C for 4, 6 and 8 hours. After heating it was cooled down to room temperature, amd the product was taken to check percentage yield by the Nuclear Magnetic Resonance Spectrometer. In case of using the catalysts, cobalt acetate, zinc acetate and stannous chloride were used. The results showed that the degradation with the catalysts obtained percentage yield of product, diethylene terephthalate (DET), higher than without catalyst for this purpose than zinc acetate and stannous chloride, respectively. The DET yield increased with an increase in the reaction time.